Adverse effects of immunosuppression after liver transplantation. (October 2021) - Noble, Johan; Terrec, Florian; Malvezzi, Paolo; Rostaing, Lionel
Abstract: After solid organ transplantation the cornerstone of immunosuppression is based on calcineurin inhibitors (CNIs), mostly tacrolimus. However, CNIs have a very narrow therapeutic window. The most important and serious side-effects of CNIs are nephrotoxicity, high blood pressure, post-transplant diabetes mellitus (PTMD), i.e., new-onset diabetes after transplantation (NODAT), dyslipidemia, and modification to the cardiovascular-risk profile. In this review, we will focus on tacrolimus-related toxicities in the setting of liver transplantation.